L. Kriel, The “Malaboch” books: Kgaluši in the “civilization of the written word” (Missionsgeschichtliches Archiv 13. Studien der Berliner Gessellschaft für Missionsgeschichte): An Interesting and Fresh Excursion into Intellectual History (Historia, 2021)
An Interesting and Fresh Excursion into Intellectual History. History is all about Context Reading Missionary Sources.
Keywords: Intellectual History; Context Reading; Missionary Sources